Type A aortic dissection: involvement of carotid artery and impact on cerebral malperfusion. (September 2021) - Munir, Wahaj; Chong, Jun Heng; Harky, Amer; Bashir, Mohamad; Adams, Benjamin
Acute type A aortic dissection is a surgical emergency and management of such pathology can be complex with poor outcomes when there is organ malperfusion. Carotid artery involvement is present in 30% of patients diagnosed with acute type A aortic dissection, and given its emergency and complex nature, there is much controversy regarding the approach, extent of treatment, and timing of the intervention. It is clear that the occurrence of cerebral malperfusion adds an extra layer of complexity to the decision-making framework for treatment. Standardization and validation of the optimal management approach is required, and this should ideally be addressed with large-scale studies. Nonetheless, current literature supports the need for rapid recognition and diagnosis of acute type A aortic dissection with cerebral malperfusion, immediate and extensive surgical repair, and the appropriate use of cerebral perfusion techniques. This paper aims to discuss the current evidence regarding the impact of carotid artery involvement in both the management and outcomes of acute type A aortic dissection.